Les « territoires créatifs » à l’échelle transfrontalière - Thomas Perrin (Territoire en Mouvement, 2013)
This article deals with the cultural actions developed in the context of euroregions and transposes the “creative territories” issue to the European cross border scale. It focuses, in particular, on two contemporary case studies : Pyrénées-Méditerranée euroregion, located at the Eastern franco-spanish border, and Greater Region that comprises Luxemburg and sub-state entities from Belgium, France and Germany. The first part discusses the notion of cultural developement, as well as the parallelisms between the models of euroregional cultural development and more general models : “Creative” vs. “Participatory” City, functional vs. cultural identity in the geo-strategic construction of territories, and the different uses of territories as cultural resources in a context of economic competition and territorial differentiation. Furthermore, the analysis shows how the evolution of cultural development impacts the euroregional cultural action, through a certain renewal of the role of cultural and artistic actions within broader issues : sustainability and environmental responsibility of tourism policies, cultural diversity and multiculturalism, construction of territoriality. Finally, euroregional cultural action relates to the construction of a European cultural and territorial polity.